Evaluation of Student Satisfaction in Using the Learning Management System for Online Learning at XYZ University - Togar Alam Napitupulu, Yulyanty Chandra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research is to analyse what factors that influence the student satisfaction with the learning management system and how much influence do these factors have on student satisfaction with the use of the learning management system. This research aim was to find if there is a direct influence from the system quality, information quality, service quality, and perceived ease of use into the user satisfaction and whether there is an indirect influence from System use to the User satisfaction toward learning management system. The analytical method for analyse regression with the estimation of PLS Method, this research took sample of 99 students at XYZ University in Information system online learning, major study for undergraduate students. The results show that the indirect effect through system use are not significant; however the perceived ease of use and system quality turn out significant affecting the student satisfaction. Perceived ease of use is the most high factor for affecting the satisfaction of the students to use Learning Management System(LMS) as the media for online learning.